MRO Procurement Engine - POOJA SINGH (2004)
INTERNAL GUIDE : M E Pauline M. EXTERNAL GUIDE: Jeyaseelan J USN No : 1MJ03SCS11 CARRIED OUT AT : Wipro Infotech Bangalore -560 027 ACC NO : PC17
Keywords: M.Tech Computer Science